Polinização do dendezeiro por besouros no sul da Bahia - Moura, José Inácio Lacerda; Cividanes, Francisco Jorge [UNESP]; Santos Filho, Lindolfo Pereira dos; Valle, Raul Rene (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2008)
O objetivo deste trabalho foi determinar a taxa de fecundação de dendezeiros, após introdução de Elaeidobius kamerunicus, no Sul da Bahia, e a flutuação populacional, distribuição espacial e a influência de fatores meteorológicos sobre E. kamerunicus e E. subvittatus. Análises físicas de 12 mil espiguetas de dendezeiros foram realizadas em 2004-2006. Na avaliação da relação entre a temperatura média mensal e o total mensal de indivíduos de E. kamerunicus e E. subvittatus, utilizou-se a correlação de Pearson. A taxa de fecundação foi de 79,4%, um incremento de 19% quando comparado aos dendezeiros polinizados apenas por E. subvittatus. Plantios comerciais de dendezeiros em Ituberá e Nazaré, BA, apresentaram taxas médias de fecundações de 76%. E. kamerunicus foi dominante nos plantios de dendezeiro de Una, BA. Populações de E. kamerunicus sobrepujaram as de E. subvittatus, em todos os municípios onde existem grandes maciços de dendezeiros subespontâneos. No entanto, em Itapebi, BA, as populações de E. subvittatus superaram as de E. kamerunicus. A temperatura e a precipitação pluvial afetam a atividade de vôo e densidade populacional de E. subvittatus.

The objective of this work was to determine the fertilization rate of oil palm trees, after the introduction of Elaeidobius kamerunicus in Southern Bahia, Brazil, and the population fluctuation, spatial distribution and the influence of meteorological factors on E. kamerunicus and E. subvittatus. Physical analyses of 12 thousand oil palm spikelets were accomplished during 2004-2006. Pearson correlation was used to evaluate the relation between monthly average temperatures and monthly totals of E. kamerunicus and E. subvittatus individuals. The fertilization rate was 79.4%, an increase of 19% when compared to palm trees pollinated only by E. subvittatus. Commercial plantations of oil palm, in Ituberá and Nazaré, BA, presented 76% mean rates of fertilization. E. kamerunicus was the dominant species in the plantations of Una, BA. Populations of E. kamerunicus overwhelmed E. subvittatus ones in all the municipalities where there are great areas of subspontaneous palm oil. However, in Itapebi, BA, populations of E. subvittatus exceeded those of E. kamerunicus. Temperature and rainfall affected the flight activity and the population density of E. subvittatus.
Pollination of oil palm by weevils in southern Bahia, Brazil
Keywords: Elaeidobius kamerunicus; Elaeidobius subvittatus; Elaeis guineensis; Meteorological factors; Population fluctuation; fecundation rate; Elaeidobius kamerunicus; Elaeidobius subvittatus; Elaeis guineensis; condições meteorológicas; Flutuação populacional; Taxa de fecundação